The performance of the EBTT Teacher in Specialized Educational Service carried out by the Federal Institute of Alagoas (Research, Society and Development, 2022)
In Federal Institute of Alagoas, specialized educational assistance to Target-Public Special Education students is carried out through the Specific Educational Needs Assistance Center (NAPNE). In the field of special and inclusive education, it is essential to have a Special Education teacher in the development of activities. Thus, this article aimed to reflect on the need for the work of the EBTT professor at NAPNE in Federal Institute of Alagoas-IFAL, highlighting teamwork and how NAPNE's actions are currently structured. It consists of a documental research, with a qualitative approach. The normative documents referring to the role of NAPNE in the institution were surveyed. The results showed that the Specialized Educational Service is fragile, despite the institutional effort in the face of the existing reality and resources, as the NAPNE sector does not have the presence of specialized technicians who are dedicated only to this activity, in addition to the absence of the special education teacher in the institution's faculty. Currently, NAPNE has, in the vast majority of members, a voluntary nature, in which the servers participate if they want, which makes the adequate service of students precarious. In addition, the PEI, which should be the responsibility of the special education teacher, is placed under the responsibility of NAPNE, without defining the responsible actor, disregarding that the activities of application, monitoring, literacy, literacy and mathematics are teaching activities of special education, because it is an activity that must be performed after school hours and applied by a special education teacher.